3 Bridging the gap between drama students and simulated patients. (17th November 2016) - Websdale, Daniel; Major, D; Purva, M
Abstract : Aim: Simulation based education has an increasing demand for the use of simulated patients. Sanson-Fisher and Poole (1980) highlighted that 'they can simulate scenarios that may be distressing for a real patient, such as bereavement'. We brought in drama students to act as patients; many of them having no previous experience of being an SP. The courses are delivered in real time; therefore there is only a small margin for error. Therefore, there was a need for a course to bridge the gap in knowledge and help them to upskill to become experienced SPs. Objectives: Run a half day course highlighting the roles and importance of simulation and SPs in scenarios. Increase confidence and knowledge of actors to undertake the SP role. Summary of Work Undertaken The course held a mixture of lectures and workshops and ended with putting theory into practice; allowing all actors to participate in a simulation scenario as an SP. The delegates completed a pre and post course questionnaire which has Likert scales of 1 to 5; with a total of 8 delegates attending the course. Results: The mean post course answers showed an improvement on every question. The table shows the percentage of how many people chose 1--3 (1 not confident to 3 average) on the Likert scale and for each of the questions there was at least a 50% improvement when they answered the post course questionnaire. Conclusions: Confidence levels of being an actor only increased marginally; however as the delegates in the pilot study were drama students it can be argued that their confidence levels were high to begin with. If the pilot study did not use drama students then the confidence levels may have increased more. It could be beneficial to conduct a short survey with the actors three months after to determine what they found most useful now they are acting as SP's. Then use that information to change the course to suit their needs. Reference: Sanson-Fisher RW, Poole AD. Simulated patients and the assessment of medical students' interpersonal skills. Medical Education 1980, 14, Page 250.